Experimental Evaluation of Novel Master‐Slave Configurations for Position Control under Random Network Delay and Variable Load for Teleoperation - Kuzu, Ahmet; Bogosyan, Seta; Gokasan, Metin; Sabanovic, Asif (Wiley, 2014)
This paper proposes two novel master‐slave configurations that provide improvements in both control and communication aspects of teleoperation systems to achieve an overall improved performance in position control. The proposed novel master‐slave configurations integrate modular control and communication approaches, consisting of a delay regulator to address problems related to variable network delay common to such systems, and a model tracking control that runs on the slave side for the compensation of uncertainties and model mismatch on the slave side. One of the configurations uses a sliding mode observer and the other one uses a modified Smith predictor scheme on the master side to ensure position transparency between the master and slave, while reference tracking of the slave is ensured by a proportional‐differentiator type controller in both configurations. Experiments conducted for the networked position control of a single‐link arm under system uncertainties and randomly varying network delays demonstrate significant performance improvements with both configurations over the past literature.